Comparison of two different doses of dexmedetomidine (0.25 mcg/kg and 0.5 mcg/kg) in prolonging duration of spinal anaesthesia and postoperative analgesia in patients undergoing trans urethral resection of prostate: a prospective randomized double blinded study - Bhiwal, Anil K.; Sharma, Karuna; Rathore, Vikram S.; Patel, Chintan M. K.; Chhabra, Alka; Jaitawat, Swai S. (International Journal of Research in Medical Sciences, 2021)
Background: Trans urethral resection of prostate (TURP) under spinal anaesthesia (SAB) in elderly with associated cardio-pulmonary, endocrine or other co-morbidities induces detrimental physiological and psychological stress response to surgery and anaesthesia. Proper sedation during spinal anaesthesia can reduces this response. Aim of this study was to compare the characteristics of spinal block, hemodynamic changes, and postoperative analgesia, following administration of intravenous DMT (0.25 mcg/kg and 0.5 mcg/kg) in elderly patients undergoing TURP under SAB. Methods: Sixty-eight patients were randomly allocated to two groups of 34 patients each. After giving spinal anaesthesia patients received two different doses of dexmedetomidine intravenously; 0.25 mcg/kg (Group D25) and 0.50 mcg/kg (Group D50) respectively. Drugs were given slowly in dilution of 10ml normal saline. Patients were monitored for intraoperative haemodynamics, sensory and motor block characteristics and postoperative analgesia in terms of VAS (visual analogue scale) and first and total dose of rescue analgesic. Results: Mean value of lowest HR in Group D50 and D 25 was comparable (p=0.11) and time taken to achieve lowest HR was also comparable (p=0.13). Mean value of lowest SBP, DBP and MAP were lower in Group D50 than in Group D25 but the difference did not reach statistical significance (p=0.52,0.95 and 0.41 respectively). Onset of sensory block was comparable between the two groups, p=0.62. Maximum sensory block was achieved significantly earlier in Group D50 (10.64±2.75 min versus 12.94±3.04 min in Group D25), p=0.0012. Group D50 patients achieved Bromage score 3 earlier (10.735±1.797 min) than group D25 (12.794±2.52 min) (p=0.00). Recovery from motor block was found earlier in Group D25 group (141.325±4.97 mins) compared to Group D50 (154.41±8.143 mins). Group D50 reported significantly higher sedation than group D25 (p=0.00). Group D25 reported more pain at 4 hours compared to Group D50 (VAS -4.705±0.462 versus 2.588±1.478). Time of requirement of first rescue analgesia was delayed in Group D50 (270.59±50.78 mins) than in Group D25 (172.50±10.46 mins), p=0.000. Conclusions: Dexmedetomidine is effective in relieving anxiety in elderly patients undergoing TURP under spinal anaesthesia. Dose of 0.50 mcg/kg is more effective than 0.25 mcg/kg without increasing the risk of adverse effect.